PENGARUH PERSEPSI SISWA TENTANG KEPRIBADIAN GURU TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA - Nasrulloh; Ade Susanti (Pendidikan Matematika | STKIP YM Bangko, 2016)
This study aims to determine the effect of student perceptions of the teacher's personality on students' mathematics learning motivation. The research method is descriptive correlational with a quantitative approach. The population in this study were all students of class VIII of SMP Negeri 4 Merangin. The sampling technique was random sampling. Data collection used the questionnaire method for variables X and Y variables. Data were analyzed using spearman rank correlation with a significant level of 5% and followed by simple regression. The results of the calculation of Spearman rank correlation are obtained as big as, whereas for simple regression a linear equation is obtained. The correlation coefficient of 0.455 states that each addition of one score or the personality value of the teacher will give an increase of 0.455. For the significance test obtained F count <F table or 0.4736 <1.77 which means Ho is rejected and H1 is accepted. Keywords: students' perceptions of teacher's personality, learning motivation